Multimedia for better training - Oz Effy; White Lodie D.
Six organizations from different industries were polled about multimedia systems they had implemented for training. The study shows that the effects of multimedia training are not industry specific. The technology is highly effective. However, organisations that intend to adopt the new technology for training have to be prepared for high implementation costs
Keywords: System Analysis; Computers; Training